Can the implementation of clinical practice guidelines improve clinical competence of physicians and kidney function of patients with type 2 diabetes mellitus? - Martínez-Martínez, Petra; Cueto-Manzano, Alfonso M.; Cortés-Sanabria, Laura; Martínez-Ramírez, Héctor R.; Rojas-Campos, Enrique; Hernández-Herrera, Aurora (Frontiers in Medicine, 2022)
Background There are many clinical practice guidelines (CPGs) in Nephrology; however, there is no evidence that their availability has improved the clinical competence of physicians or the outcome of patients with chronic kidney disease (CKD). This study was aimed to evaluate the effect of implementation of CPGs for early CKD on family physicians (FP) clinical competence and subsequently on kidney function preservation of type 2 diabetes mellitus (DM2) patients at a primary healthcare setting. Methods A prospective educative intervention (40-h) based on CPGs for Prevention, Diagnosis and Treatment of Early CKD was applied to FP; a questionnaire to evaluate clinical competence was applied at the beginning and end of the educative intervention (0 and 2 months), and 12 months afterwards. DM2 patients with CKD were evaluated during 1-year of follow-up with estimated glomerular filtration rate (eGFR) and albuminuria. Results After educative intervention, there was a significant increase in FP clinical competence compared to baseline; although it was reduced after 1 year, it remained higher compared to baseline. One-hundred thirteen patients with early nephropathy (58 stage 1, 55 stage 2) and 28 with overt nephropathy (23 stage 3, 5 stage 4) were studied. At final evaluation, both groups maintained eGFR [(mean change) early 0.20 ± 19 pNS; overt 0.51 ± 13 mL/min pNS], whereas albuminuria/creatinuria (early −67 ± 155 p < 0.0001; overt −301 ± 596 mg/g p < 0.0001), systolic blood pressure (early −10 ± 18 p < 0.05; overt −8 ± 20 mmHg p < 0.05), and total cholesterol (early −11 ± 31 p < 0.05; overt −17 ± 38 mg/dL p < 0.05) decreased. Diastolic blood pressure, waist circumference and LDL-cholesterol were also controlled in early nephropathy patients. Conclusions CPGs for Prevention, Diagnosis and Treatment of CKD, by means of an educative intervention increases FP clinical competence and improves renal function in DM2 patients with CKD.